Perencanaan Geometrik Persimpanga Jalan Wahid Hasyim – Jalan H.M. Ardan di Kota Samarinda - Rosa Agustaniah (Kurva S : Jurnal Keilmuan dan Aplikasi Teknik Sipil, 2018)
Geometric improvements at the intersection of road Wahid Hasyim – H.M Ardan which is the intersection of a plot has four arms. The intersection point of this area is the Outer Ring Road connecting road to the northern region of Samarinda. Geometric improvements at this intersection is expected to resolve the conflict and reduce the rate of traffic accidents for the user.The intention of this analysis is planned at the intersection geometric road Wahid Hasyim – H.M Ardan. The purpose of this study are as follows plotting visibility at the intersection, taper at the intersection, planned right turn lane and left turn lane and the street median plan, Rumaja, Rumija, Ruwasja.